Intragroup cooperation vs. Intragroup competition A Meta-Analytical Study - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pascasarjana UGM, 2004)
This study examines whether intragroup cooperation outperforms intragroup competition. Intragroup cooperation is a work setting when individuals in a group perceive that their goal attainments are positively related